Evaluation of anticoagulant and thrombolytic activity of Berberis orthobotrys in animal model - Alamgeer, .; Tarar, Mahpara; Hasan, Umme Habiba; Saleem, Muhammad (Bangladesh Journal of Pharmacology, 2018)
Fundamental to this research was the evaluation of anticoagulant and thrombolytic potential of Berberis orthobotrys using clotting time, prothrombin time and activated partial thromboplastin time performed at 2.5, 5, 10% concentration. Aqueous-methanol extract significantly (p<0.05) increased the coagulation parameters both in human blood as well as in rabbit blood and exhibited the more salient effect on prolongation of these coagulation parameters at 10% concentration. Aqueous methanol extract (25, 50 and 100 mg/kg) produced the preferential increase in bleeding time and clotting time nevertheless the effect was more perceptible after 90 min at 100 mg/kg. Moreover, the crude extract presented a substantial increase in coagulation parameters after 7 days of administration in rabbits with more pronounced effects at the highest dose. HPLC profile of aqueous methanol extract revealed the presence of quercetin, p-coumaric acid, gallic acid, vanillic acid, 4-hydroxy-3-methoxy benzoic acid. Thus, the present study provides the pharmacological basis for its medical use in cardiovascular and other thrombotic disorders.